Glycaemic control, hypoglycaemia, and weight change with insulin glargine 300 U/mL versus insulin glargine 100 U/mL in Japanese adults with type 2 diabetes: A 12‐month comparison by concomitant sulphonylurea and/or glinide use. Issue 11 (16th July 2018) - Terauchi, Yasuo; Riddle, Matthew C.; Hirose, Takahisa; Koyama, Masayoshi; Cheng, Xi; Takahashi, Yoshinori; Bolli, Geremia B.
Abstract : Aim: To explore if clinical effects and hypoglycaemia risks associated with insulin glargine 300 U/mL (Gla‐300) and 100 U/mL (Gla‐100) differed by sulphonylurea and/or glinide (SU/G) treatment. Methods: A post hoc subgroup analysis of 12‐month treatment data from the EDITION Japan 2 trial, a randomized, open‐label, phase 3 study of Japanese people with type 2 diabetes receiving once‐daily Gla‐300/Gla‐100 + oral antihyperglycaemic drugs. Participants previously receiving SU/G (+SU/G) were compared with those not taking SU/G (‐SU/G). Endpoints included HbA1c, hypoglycaemia and body weight. Results: For +SU/G (n = 152, 63%), HbA1c was reduced from baseline to month 12 for Gla‐300 (8.1% to 7.6%) and Gla‐100 (8.2% to 7.8%). For ‐SU/G (n = 89, 37%), reductions were 7.8% to 7.4%, and 7.9% to 7.5% for Gla‐300 and Gla‐100, respectively. A lower annualized rate of hypoglycaemia with Gla‐300 versus Gla‐100 was observed at night (00:00–05:59 hours; p = 0.0001) and any time of day (24 hour; p = 0.0015). Irrespective of the insulin used, the incidence and rate of confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemia appeared higher in +SU/G versus ‐SU/G; overall, a reduced incidence of nocturnal hypoglycaemia, and rate of hypoglycaemia at any time, was observed in ‐SU/G versus +SU/G. In the ‐SU/G subgroup, body weight gain differences were observed between Gla‐300 and Gla‐100 (p < 0.0001). Conclusions: Participants with prior and continued SU/G use had similar therapeutic responses with basal insulin but greater risk of hypoglycaemia than those not using SU/G; hypoglycaemia risk was lower with Gla‐300 than Gla‐100 in both subgroups.